Demographic Crisis, Causes of Death Among the Population - Dilshoda Inomjonova (Zien Journals, 2022)
in this article, the scientific practical basis of demography, demography, the essence of the concept of demography, the tension that arises in demography, its development, demographic processes, the reproduction of the population, the incidence of death in the structure of demographic processes, the origin of demographic tension. the origin of cases of death.
Keywords: population; geography o f population; economic-social geography; productive forces